Coliforms in cremoladas sold in the city of Jaen, 2025 - Bravo Vasquez, Jarly (2025)
In the province of Jaén, department of Cajamarca, temperatures can exceed 35 °C. Due to the intense heat, residents choose to consume cremoladas, made with ice, flavorings and/or pure fruit, and which are often not prepared with adequate care and sanitary measures. Given the high demand for these drinks, we were forced to conduct a descriptive, non-experimental study aimed at determining the presence of coliforms in cremoladas sold in the city of Jaén. 64 samples from different points of sale in the city of Jaén were evaluated. Two repetitions were made to count coliforms and Escherichia coli, homologating them with NTS No. 071 - MINSA/DIGESA-V. 01. Determinig that 87,5% of processed samples were positive for coliforms with a maximum count of 118x103 UFC/ml and a minimun of 1x101 UFC/ml, the presence of Escherichia coli was identitified in 37,5%, Entorobacter cloacae 23,5%, Citrobacter koseri 28,4%, and Shiguella sp. 70,6%, therefore, it is conclued thra the cremoladas are not suitable for human consumption according to NTS N° 071-MINSA/DIGESA-V.01